2013
DOI: 10.1016/j.bbadis.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of model organisms for the study of neuronal ceroid lipofuscinosis

Abstract: Neuronal ceroid lipofuscinoses are a group of fatal progressive neurodegenerative diseases predominantly affecting children. Identification of mutations that cause neuronal ceroid lipofuscinosis, and subsequent functional and pathological studies of the affected genes, underpins efforts to investigate disease mechanisms and identify and test potential therapeutic strategies. These functional studies and pre-clinical trials necessitate the use of model organisms in addition to cell and tissue culture models as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 313 publications
1
73
0
Order By: Relevance
“…Previous studies using mouse and Drosophila models of Batten disease have revealed that synaptic disruption is intimately linked to the regional onset of neurodegeneration (Cooper 2010; Bond et al. 2013), with our findings demonstrating that the relationship between synaptic pathology and neurodegeneration is likely to be similarly conserved in CLN5 sheep. However, given the symptomatic nature of the sheep investigated in this study, further studies examining synaptic changes at pre and early‐symptomatic time points will now be required in order to establish whether synaptic loss precedes, or occurs concurrently with, gross neuropathological changes.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous studies using mouse and Drosophila models of Batten disease have revealed that synaptic disruption is intimately linked to the regional onset of neurodegeneration (Cooper 2010; Bond et al. 2013), with our findings demonstrating that the relationship between synaptic pathology and neurodegeneration is likely to be similarly conserved in CLN5 sheep. However, given the symptomatic nature of the sheep investigated in this study, further studies examining synaptic changes at pre and early‐symptomatic time points will now be required in order to establish whether synaptic loss precedes, or occurs concurrently with, gross neuropathological changes.…”
Section: Discussionsupporting
confidence: 73%
“…2011; Bond et al. 2013). Batten disease often refers to a group of fatal neurodegenerative disorders that mainly begin in childhood, representing the most common group of childhood neurodegenerative diseases, also collectively known as the neuronal ceroid lipofuscinoses (NCLs) (Palmer et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As no one has yet demonstrated overt seizures or retinal degeneration in the mouse model [21], this zebrafish model is potentially more relevant to the disease than the mouse model.…”
Section: Cln2 Diseasementioning
confidence: 99%
“…Compared to disease onset at 7 weeks in the mouse model [21], the embryonic onset and fast progression in the zebrafish model offers the potential to complete experiments much more quickly.…”
Section: Cln2 Diseasementioning
confidence: 99%